2022
DOI: 10.3390/agronomy12010151
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 50 Years of No-Tillage, Stubble Retention, and Nitrogen Fertilization on Soil Respiration, Easily Extractable Glomalin, and Nitrogen Mineralization

Abstract: In subtropical regions, we have an incomplete understanding of how long-term tillage, stubble, and nitrogen (N) fertilizer management affects soil biological functioning. We examined a subtropical site managed for 50 years using varying tillage (conventional till (CT) and no-till (NT)), stubble management (stubble burning (SB) and stubble retention (SR)), and N fertilization (0 (N0), 30 (N30), and 90 (N90) kg ha−1 y−1) to assess their impact on soil microbial respiration, easily extractable glomalin-related so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 58 publications
1
3
0
Order By: Relevance
“…Soil microbial respiration was used as an indicator of microbial activity in the soils of the three treatments. Our findings are in accordance with the literature, that soil microbial respiration is typically higher in NT when compared to reduced tillage (SC in this case) or P [50,51].…”
Section: Biological Parameterssupporting
confidence: 93%
“…Soil microbial respiration was used as an indicator of microbial activity in the soils of the three treatments. Our findings are in accordance with the literature, that soil microbial respiration is typically higher in NT when compared to reduced tillage (SC in this case) or P [50,51].…”
Section: Biological Parameterssupporting
confidence: 93%
“…In contrast, a long-term experiment conducted by Jha et al [69] over a period of fifty years did not align with previous studies, wherein higher respiration rates were seen in treatments where stubble remained after harvesting, likely due to more organic material being available in the soil. However, in this study, there was not a notable difference in the overall organic carbon content between treatments where stubble was burnt and those where it was not.…”
Section: Effect On Soil Microbial Communitiescontrasting
confidence: 86%
“…This could point towards greater stability of glomalin against mineralization than other soil organic matter. Jha et al [66] found a positive correlation between the mineralization process (release of nitrogen from organic bonds) and EEG content. Authors further concluded that EEG content could be a certain criterion for estimating potential nitrogen mineralization from organic bonds.…”
Section: Relationship Between Glomalin and Som Parametersmentioning
confidence: 99%